La question et l’interrogation en contexte : point de vue énonciatif - Jean-Marie Merle (Corela)
This paper sets out to examine questions and interrogation from an enunciative perspective: the various types of structuration are presented in connection with their enunciative and pragmatic – modal and illocutionary – implications. It examines the relevance of epistemic modality, and explores the underlying plurimodality which motivates questions and interrogation, and in what way illocutionary force builds up, and can be neutralised in percontative clauses (interrogative content clauses). It sheds light on the inter-enunciative relation and the way it is exploited.